2001
DOI: 10.1093/emboj/20.1.272
|View full text |Cite
|
Sign up to set email alerts
|

A novel clathrin homolog that co-distributes with cytoskeletal components functions in the trans-Golgi network

Abstract: A clathrin homolog encoded on human chromosome 22 (CHC22) displays distinct biochemistry, distribution and function compared with conventional clathrin heavy chain (CHC17), encoded on chromosome 17. CHC22 protein is upregulated during myoblast differentiation into myotubes and is expressed at high levels in muscle and at low levels in non-muscle cells, relative to CHC17. The trimeric CHC22 protein does not interact with clathrin heavy chain subunits nor bind significantly to clathrin light chains. CHC22 associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
96
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 46 publications
20
96
1
2
Order By: Relevance
“…Hence, this data suggests the possibility of a new, additional function of CLTC in the context of autophagy. Recent studies have demonstrated that CLTC exists in 2 isoforms, CHC17 and CHC22, and that these isoforms have different functions [30,31]. CHC17 binds to clathrin light chains (CLC) and AP2 at the plasma membrane for endocytosis, however CHC22 binds neither CLC or AP2 and has been described to aid in trafficking of SLC2A4/GLUT4 (solute carrier family 2 member 4) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this data suggests the possibility of a new, additional function of CLTC in the context of autophagy. Recent studies have demonstrated that CLTC exists in 2 isoforms, CHC17 and CHC22, and that these isoforms have different functions [30,31]. CHC17 binds to clathrin light chains (CLC) and AP2 at the plasma membrane for endocytosis, however CHC22 binds neither CLC or AP2 and has been described to aid in trafficking of SLC2A4/GLUT4 (solute carrier family 2 member 4) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Given the ability of VSV-G to usurp the function of the putative AP-3-regulated pathway, we suggest that it is both the type of cargo and the type of coat that dictates the targeting information recruited to or retained in carrier intermediates exiting the TGN. Indeed, two distinct classes of AP-3-coated structures, clathrin-associated and clathrin-independent AP-3s, have been reported (61), and a third may involve a novel form of clathrin (62). Thus, a combination of cargo, AP-3, and other coat components may favor coassembly with specific vesicle targeting proteins that direct the fate of the transport container to either the lysosome (yeast vacuole) (i.e., LAMP1), regulated secretory lysosome (i.e., tyrosinase), or constitutive pathways (VSV-G, other?).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by DeWan et al, it was found that one mutation, I303L, in PDE4DIP may be the causative variant in hereditary asthma (23). CLTCL1 is a member of the clathrin family, which plays essential roles in intracellular traffic and centrosomal stabilization (24). Mutations or the abnormal expression of CLTCL1 have been reported to be associated with breast cancer, meningioma and pulmonary valve stenosis (25).…”
Section: Discussionmentioning
confidence: 99%